1999
DOI: 10.1074/jbc.274.12.7741
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans Differentially Bind HARP and Modulate Its Biological Activity

Abstract: Heparin affin regulatory peptide (HARP) is a polypep-) and a lower affinity (K d ‫؍‬ 51 nM). Exogenous heparin, heparan sulfate, and dermatan sulfate potentiated the growth-stimulatory activity of HARP, suggesting that corresponding proteoglycans could be involved in the regulation of the mitogenic activity of HARP. Heparin affin regulatory peptide (HARP)1 belongs to a growing group of heparin binding extracellular regulatory molecules, and it has mitogenic and neurite outgrowth activities.Independently purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 45 publications
1
41
1
4
Order By: Relevance
“…Each ␤-sheet domain contains a heparin-binding site, which plays a role in the modulation of HARP mitogenic activity (20). In addition, we have shown that at least one heparin-binding domain is involved in the dimerization of HARP (21).…”
mentioning
confidence: 93%
“…Each ␤-sheet domain contains a heparin-binding site, which plays a role in the modulation of HARP mitogenic activity (20). In addition, we have shown that at least one heparin-binding domain is involved in the dimerization of HARP (21).…”
mentioning
confidence: 93%
“…Western Blot Analysis and ELISA The PTN expression in supernatants, cell pellets, and extracellular compartments defined as cell surface and extracellular matrix MDA-MB-231 tumors was done in MDA-MB-231 and PC3 cells by Western blot analysis following heparin Sepharose precipitation as described previously (20). Quantification of the immunoreactive material was done by densitometric analysis using a ChemiGenius system and the Genetools software (Syngene).…”
Section: Methodsmentioning
confidence: 99%
“…DS from porcine skin shows negligible binding to immobilized MK compared with CS-H (12), although the 3 M NaCl-eluted fraction was used previously. On the other hand, DS from porcine skin binds PTN with a K d of 51 nM when DS is immobilized on the sensor's surface (39).…”
Section: Specific Interactions Of Cs-h With Variousmentioning
confidence: 99%